Planning stages of a proposed sports training soccer - Naji, Deyaa; Kadhim, Emad; Ashraf, Nazar (Journal of Physical Education, 2015)
Planning in Soccer – training played very important role in the achievement. the research aim to propose the planning phases of soccer –trainning.It has been explained these phases on sample from trainers partsicipation in the training course (B) of Asian federation in soccer and then distributed the questionnaire and after that the researchers concluded that the proposed phases helped the trainers in planning their curriculum training in soccer